The Crucial Role of Plaque Control in Peri-Implant Mucositis Initiation as Opposed to the Role of Systemic Health Condition: A Cross-Sectional Study - AbdulAzeez AR; Alkinani AA (Clinical, Cosmetic and Investigational Dentistry, 2021)
Ali Raad AbdulAzeez,1 Athil Adnan Alkinani2 1Department of Periodontology, College of Dentistry, University of Uruk, Baghdad, Iraq; 2Department of Oral and Maxillofacial Surgery, College of Dentistry, University of Uruk, Bagdad, IraqCorrespondence: Ali Raad AbdulAzeezDepartment of Periodontology, College of Dentistry, University of Uruk, St.52, Al-Wihda District, Baghdad, IraqTel +9647901635737Email aliraadabdulazeez@uruk.edu.iqPurpose: The aim of this study was to investigate the priority of periodontal plaque as a risk factor compared to other risk factors, namely hypertension and diabetes mellitus type II, regarding the initiation and severity of peri-implant mucositis, eventually reinforcing the importance of plaque control, periodic maintenance and supportive periodontic treatment after implant placement in order to prevent peri-implant diseases.Patients and Methods: A total of 58 patients (84 implants) were enrolled; each individual implant was considered as a separate sample first, then sampling by patient was also applied, implants were divided into group A: systemically healthy patients and B: patients with hypertension and diabetes mellitus type II, the status of peri-implant tissue was followed after the healing abutment placement, with regard to implant mucosal index (IMI), probing pocket depth (PPD) and bleeding on probing (BOP); when sampling was done by patient, the mean of scores of all examined implants in each patient was taken to represent one sample.Results: Group A implants showed higher mean scores of PPD (5.2 mm) than group B (4.2 mm) with significance (P = 0.014), and higher mean scores of BOP, group A = 0.71, group B = 0.45 with (P = 0.015); there was no statistical difference with regard to IMI, group A = 1.35, group B = 1.16 with (P = 0.172). Similar results were obtained when the sampling was calculated by patient; PPD: group A (5.31 mm), group B (4.75 mm) and P = 0.008, IMI: group A (1.34), group B (1.16) and P = 0.131, BOP: group A (0.75), group B (0.48) and P = 0.03.Conclusion: In the absence of proper plaque control, systemic diseases showed no impact on the initiation and severity of peri-implant mucositis when compared to systemically healthy patients.Keywords: mucositis, dental implant, dental plaque, risk factor